The Role of Strategic Management in Improving the Quality of Islamic Education: A Literature - Fathoni, Muhammad; Kubro, Fauziyatul; Wulan Meilani, Inta; Kusumaningrum, Hesti (Khalifah : Jurnal Pendidikan Nusantara, 2025)
Islamic education plays a strategic role in shaping high-quality human resources (HR), not only excelling in intellectual aspects but also possessing noble character in accordance with the values of Islamic teachings. In facing the challenges of globalization and the advancement of science and technology, Islamic education is required to develop a holistic and integrative paradigm, internalizing the values of faith, noble character, and spirituality in every dimension of the learning process. Improving the quality of Islamic education becomes an unavoidable agenda to ensure that educational institutions are capable of producing competent graduates who contribute to society. This study aims to examine the role of strategic management in enhancing the quality of Islamic education, using a qualitative approach through literature review. The findings of the study indicate that strategic management plays a crucial role in formulating structured and systematic policies to achieve the goals of Islamic educational institutions. The implications of this research highlight the importance of applying comprehensive strategic management in Islamic educational institutions to create sustainable education quality that meets the demands of the times.